Geochronology and Geochemistry of the Jiachadui Ganodiorite in Xizang and its Geological Implications - YONGZHONGLADA; Junyong LU; SUOLANGDUNDAN; Xinghai LUO; Jianhua ZHU (Kuangchan zonghe liyong, 2024)
This is an article in the field of earth sciences. Magmatic rocks of the Gondwana Belt are one of the most popular problems in basic geological research on the Xizang-Qinghai Plateau. In this paper, we analyze the physical origin and regional tectonic properties of the Gachatai granite using LA-ICP-MS zircon U-Pb dating method, combined with the geochemical characteristics of the rocks and various graphical methods. The rocks are characterized by high alkali (average Na2O+K2O content of 6.26%), potassium (K2O/Na2O=1.03), low TiO2 (average 0.50%) and quasi-aluminous (aluminum saturation index A/CNK=0.933～1.033, average 0.991) high potassium-calcium-alkaline rock system. Rare earth elements show negative anomalies at Eu, which is the Eu-deficient type, and Ce has weak negative anomalies; trace elements show enrichment of large ion-parental elements Rb, Th, Nd, La and K; high field strength elements Nb, Ba, U, Ta, Ce, Sm and Ti are deficient; reflecting the mixed crust-mantle type of magma origin and the presence of subduction oceanic crustal melting. The zircon LA-ICP-MS U-Pb isotopic age is （345.3±1.8） Ma, and its formation age is Early Carboniferous. The analysis of the regional geological data suggests that this magmatic event is a product of the formation of the northern part of the eastern Gondwana continent after the breakup of the Rodinia supercontinent. The project points go to I-type granite, the discriminant diagrams indicate it’s formed from continental island arc, going through time before plate collision to co-collisional orogenic movement, which indicates a long period time of magmatic evolution; the rock geochemical characteristics show the environment of magmatic evolution changed from the start of island arc(primary island arc)-development(early stage island arc)-maturement(full-grown island arc).